A systematic literature review to identify psychological impact of cyberbullying - Dewa Ayu Aristya Prabadewi; Endang Retno Surjaningrum (Universitas Negeri Padang, 2022)
Cyberbullying in adolescents is said to cause various negative impacts. This literature review aims to summarize current information about the psychological impact of cyberbullying in adolescents. A systematic literature search was conducted on the electronic databases of Science Direct, ProQuest, Sage Pub, and Google Scholar. Screening and selection were carried out to produce 14 relevant articles published in 2018-2023. Most of the articles reported findings on the psychological impact of cyberbullying in adolescents, such as psychosomatic symptoms, emotional problems, behavior problems, suicidal ideation and attempts, and psychosocial impact. Several studies have also highlighted the psychological impact on the bullys.